The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1002/chem.201706143
|View full text |Cite
|
Sign up to set email alerts
|

Photoluminescence of Visible and NIR‐Emitting Lanthanide‐Doped Bismuth‐Organic Materials

Abstract: A bismuth-organic compound containing 2,2':6'2"-terpyridine (terpy) and 2-thiophenecarboxylate (TC), of the general formula (terpy)Bi(κ -TC) ⋅0.47 H O (BiOM-1), has been synthesized under hydrothermal conditions. Addition of a lanthanide nitrate solution to the reaction mixture led to statistical replacement of the bismuth centers, and yielded isomorphous lanthanide containing compounds Bi Ln OM-1 (Ln=Nd, Sm, Eu, Tb, Dy, Er, and Yb) that showed bismuth and/or ligand sensitized lanthanide-centered emission, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 55 publications
2
26
0
Order By: Relevance
“…[65][66][67][68] We have also previously reported a mixed ligand Bi-terpy-thiophenemonocarboxylate compound. 37 The structural unit of 3 is isostructural to the bromobismuth-phen dimer published by White et al, [Bi 2 Br 6 ( phen) 4 ], though attempts by the authors to produce the chloride analog were reportedly unsuccessful. 42 Interestingly, the chlorobismuth dimer is accessible using terpy as a capping ligand, possibly owing to the increased denticity and ability of terpy to better saturate the metal coordination sphere.…”
Section: Structure Descriptionsmentioning
confidence: 97%
See 1 more Smart Citation
“…[65][66][67][68] We have also previously reported a mixed ligand Bi-terpy-thiophenemonocarboxylate compound. 37 The structural unit of 3 is isostructural to the bromobismuth-phen dimer published by White et al, [Bi 2 Br 6 ( phen) 4 ], though attempts by the authors to produce the chloride analog were reportedly unsuccessful. 42 Interestingly, the chlorobismuth dimer is accessible using terpy as a capping ligand, possibly owing to the increased denticity and ability of terpy to better saturate the metal coordination sphere.…”
Section: Structure Descriptionsmentioning
confidence: 97%
“…Beyond their precedence in luminescent materials research, [32][33][34][35] these ligands have been shown to restrict dimensionality through capping coordination modes to yield molecular units. [36][37][38][39][40] Moreover, the aromaticity of the ligands may promote supramolecular interactions such as π-π stacking, which have been shown to impact the materials properties of hybrid inorganic-organic complexes. 41 The obtained compounds,…”
Section: Introductionmentioning
confidence: 99%
“…[ 1–4 ] Since then, a number of publications presented coordination compounds of Eu 3+ with terpyridine itself or its derivatives. [ 5–18 ] In these compounds, trivalent europium as 4f‐4f emitter is influenced by the chemical environment rather in the intensity of 4f‐4f transitions than in nature of the transitions. [ 19–21 ] In addition, terpyridine and its derivatives are good sensitizers of trivalent Eu 3+ photoluminescence properties.…”
Section: Introductionmentioning
confidence: 99%
“…They emit throughout the visible and NIR, and some of the typical NIR emitters also have possible transitions in the visible range,, but these are usually too weak to be readily observed. Terpyridine and its derivatives are known to enhance trivalent lanthanide luminescence, but mostly photophysical properties of these compounds are well studied for the standard visible emitters, such as Eu 3+[6–14] and Tb 3+ , whereas other rare earth metal ions such as Er 3+[13–16] or Tm 3+[17] have been investigated to a lesser extent. For the ligand 4′‐phenyl‐2,2′:6′,2′′‐terpyridine (ptpy), complexes especially with transition metals were studied .…”
Section: Introductionmentioning
confidence: 99%